PENGARUH RASIO KEUANGAN, UKURAN PERUSAHAAN, DAN REPUTASI AUDITOR TERHADAP OPINI GOING CONCERN - Aprinia, Rizki Wulan; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to examine the influence of financial ratio, firm size, and auditorâreputation to the going concern audit opinion on companies which are listed in Indonesia Stock Exchange (IDX) in 2012-2014 periods. The samples are all sector companies which are listed in Indonesia Stock Exchange in 2012-2014 periods. 1480 companies have been selected as samples by using Stratified Random Sampling method and it results 265 financial statements of the companies and it obtains 33% of going concern audit opinion. The data analysis has been carried out by using logistic regression and independent variables liquidity, profitability, solvability, and company growth ratios, firm size, auditorâreputation, and dependent variable going concern audit opinion. It has been found from the result of the research that variable liquidity, and profitability ratios, and firm size has significant influence to the going concern audit opinion whereas variable solvability, and company growth ratios, firm size, and auditorâreputation do not have any significant influence to the going concern audit opinion.Keywords:Financial ratio, firm size, auditorâreputation, and going concern audit opinion.